Qualitative Item Development for a Nurses’ Caring Behavior Scale in Patients Undergoing Chemotherapy for Cancer - Yulta Kadang; Sri Marnianti Irnawan; Irna Megawati; Kusrini S Kadar; Ariyanti Saleh (PT.Mantaya Idea Batara, 2026)
Background: Patients with cancer undergoing chemotherapy experience complex physical and psychological problems that require comprehensive nursing care. Nurses’ caring behaviors are important in improving the quality of care provided to patients. However, existing instruments for measuring caring behaviors remain limited, particularly those grounded in Swanson’s Theory of Caring. Therefore, this study aimed to develop conceptual domains and generate items to measure nurses’ caring behaviors toward patients with cancer receiving chemotherapy. Objective: To develop a new conceptual framework in the form of domains and produce statement items through a qualitative approach. Methods: This study used a phenomenological approach as the first phase of an instrument development study. In-depth interviews were conducted with 10 participants receiving chemotherapy, selected through purposive sampling. The interviews were recorded and transcribed digitally, and the data were analyzed using content analysis in NVivo 10 to identify codes, categories, and themes to develop conceptual domains and item statements. Results: A total of 33 statement items were developed from five main domains. The first domain was respect for culture (5 items); the second, information provision (6 items); the third, responsiveness (7 items); the fourth, competence (9 items); and the fifth, overall motivation (6 items). Conclusion: This study generated five domains, comprising 33 positive and negative statement items, that will be used in the questionnaire to measure cancer patients undergoing chemotherapy's perceptions of nurses' behavior.